2016
DOI: 10.1017/s1368980016002834
|View full text |Cite
|
Sign up to set email alerts
|

Controlling feeding practices and maternal migrant background: an analysis of a multicultural sample

Abstract: 4Objective: Parental feeding practices shape children's relationships with food and eating. 5Feeding is embedded socioculturally in values and attitudes related to food and parenting. 6 However, few studies have examined associations between parental feeding practices and 7 migrant background. Design: Cross-sectional study. Parental feeding practices (restriction, pressure to eat, and 9 monitoring) were assessed using the Child Feeding Questionnaire. Differences were explored 10 in four subsamples grouped b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 81 publications
3
12
1
Order By: Relevance
“…Kröller and Warschburger (47) found that the higher the mother's education, the greater the monitoring; and Musher-Eizenman et al (48) found that the higher the mother's education, the less the regulation. The finding of higher educational levels associated with greater pressuring to eat differs from other studies that did not report such an association (22,49) . High parental education has been related to health consciousness in food choices (50,51) and this observed association could be connected to pressure to eat healthy foods.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Kröller and Warschburger (47) found that the higher the mother's education, the greater the monitoring; and Musher-Eizenman et al (48) found that the higher the mother's education, the less the regulation. The finding of higher educational levels associated with greater pressuring to eat differs from other studies that did not report such an association (22,49) . High parental education has been related to health consciousness in food choices (50,51) and this observed association could be connected to pressure to eat healthy foods.…”
Section: Discussioncontrasting
confidence: 99%
“…In these countries, a scale very similar in content to ours had also been employed. These results support previous suggestions that feeding practices vary by sociocultural background (18,22) . In terms of percentages, not modelling ranked first in frequency; more than six of every ten mothers did not use modelling strategies and consumption of sweetened beverages, candy or snacks in front of the child was a common practice.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is moreover noteworthy that negative depictions of family meals, for instance, involving conflicts between family members or children not behaving in the meal situation, were hardly mentioned at all. Whereas, the ideal tells us that family meals are to be happy, warm and commensal, they may in reality entail conflict and power struggles (Wilk, ) or involve controlling feeding practices such as restrictive feeding or pressure to eat (Ek et al, ; Somaraki et al, ). However, the strong normative power surrounding family meals makes it difficult to portray the mundane nature of family meals in research, which may entail negative aspects (Wilk, ).…”
Section: Discussionmentioning
confidence: 99%